Impact of School-Based Assessment on Teaching Practices and Student Achievement in Public Sector Elementary Schools of District Khushab - Ghulam Zainab; Dr. Manzoor Raza; Abida Raza (`, 2025)
The main objective of the study was investigate school based assessment and its effects on teachers’ practices and student performance in public elementary schools. Employing a survey based approach, the research was explore how SBA implementation affects teachers' pedagogical approaches, including assessment design, feedback provision, and instructional adaptation, and examined the relationship between SBA and students learning outcomes, encompassing both cognitive and affective domains. I selected this topic because School-Based Assessment (SBA) is a crucial shift from rote memorization toward formative, learner-centered evaluation, making it highly relevant in improving both teaching practices and student performance in Pakistan’s public elementary schools. It also addresses a critical research gap by exploring how SBA can transform teachers’ instructional strategies and provide equitable learning opportunities for diverse student populations. The main hypothesis was there is no significant difference between school-based assessment practices and teachers instructional strategies, teachers’ workload in public elementary schools, the frequency of formative assessments used by teachers and students’ academic performance in public elementary schools. Population of the study was public elementary schools of district Khushab Pakistan. In sample, a convenient sampling technique was used to select the sample and collect data from 200 teachers (one head teacher, three ESTs, and one PST) of 40 elementary schools of District Khushab. There were total 108 public elementary schools in District Khushab and among them 40 public elementary schools were selected as a sample. One questionnaire was used to collect the data from head teachers and teachers. Data was collected by using random sampling technique and analyzed by using SPSS software. The data was analyzed using both descriptive (frequencies, percentages, and standard deviations) and inferential (T-test and chi-square) statistics. School-Based Assessment (SBA) is an assessment management program that has taken a growing importance in the education reform, especially in the developing nations like Pakistan where the traditional summative examinations have controlled the assessment process. In contrast to the standardized testing, SBA focuses on ongoing examination of the advancement of leaners with the help of multiple formative approaches that include classroom observations, project work, peer assessment, and reflecting feedback. The intended purpose of this shift is to facilitate meaningful learning experiences, critical thinking, and make sure that assessment facilitates learning as opposed to measuring learning. In SBA, teachers is be the proactive agents in the process of discovering the strengths and weaknesses of students and adjusting their teaching techniques to satisfy their individual learning requirements. Therefore, SBA can be used as a diagnostic and developmental instrument that can increase the overall quality of the teaching and learning processes. Implementation of SBA, however, has opportunities and challenges to teachers in the elementary schools that are publicly run. Although it allows the teachers to create context-based assessment problems and participates in reflective pedagogical activities, it also requires extra time, proficiencies, and professional dedication. The teachers in most instances might be limited by lack of training, overworking, and lack of administrative backup to carry out the implementation of SBA successfully. Thus, it is crucial to study the role of SBA in the instructional decision-making of teachers, their work organization and evaluation systems in order to comprehend the actual effect it has on the level of education. Additionally, the study of the correlation between SBA and academic and affective performance of students can give us valuable information on whether this evaluation instrument actually improves the learning process or it involves teachers in an additional procedure of complicating the tasks. The current research that centres on public elementary schools of District Khushab, therefore, plays an immense role in the rising research that aims at enhancing assessment literacy and evidence-based instruction in the education system of Pakistan. Keywords: School-Based, Assessment, Teaching Practices, Student Achievement, Public Sector, Elementary Schools.